Development and accuracy evaluation of a single-camera intra-bore surface scanning system for radiotherapy in an O-ring linac - Delombaerde, Laurence (Phys Imaging Radiat Oncol, 2019)
BACKGROUND AND PURPOSE: Current commercial surface scanning systems are not able to monitor patients during radiotherapy fractions in closed-bore linacs during adaptive workflows. In this work a surface scanning system for monitoring in an O-ring linac is proposed. METHODS AND MATERIALS: A depth camera was mounted at the backend of the bore. The acquired surface point cloud was transformed to the linac coordinate system after a cube detection calibration step. The real-time surface was registered using an Iterative Closest Point algorithm to a reference region-of-interest of the body contour from the planning CT and of a depth camera surface acquisition from the first fraction. The positioning accuracy was investigated using anthropomorphic 3D-printed phantoms with embedded markers: a head, hand and breast. To simulate clinically observed positioning errors, each phantom was placed 24 times with 0–10 mm and 0–8° offsets from the planned position. At every position a cone-beam CT (CBCT) was acquired and a surface registration performed. The surface registration error was determined as the difference between the surface registration and the CBCT-to-CT fiducial marker registration. RESULTS: The registration errors were (mean ± SD): lat: 0.4 ± 0.8 mm, vert: −0.2 ± 0.2 mm, long: 0.3 ± 0.5 mm and Yaw: −0.2 ± 0.6°, Pitch: 0.4 ± 0.2°, Roll: 0.5 ± 0.8° for the body contour reference, and lat: −0.7 ± 0.7 mm, vert: 0.3 ± 0.2 mm, long: 0.2 ± 0.5 mm and Yaw: −0.5 ± 0.5°, Pitch: 0.1 ± 0.3°, Roll: −0.7 ± 0.7° for the captured surface reference. CONCLUSION: The proposed single camera intra-bore surface system was capable of accurately detecting phantom displacements and allows intrafraction motion monitoring for surface guided radiotherapy inside the bore of O-ring gantries.